Nadawanie, pozbawianie i przywracanie obywatelstwa polskiego - Kulka, Grzegorz (Wydawnictwo Poznańskie sp. z o.o., 2011)
After the end of the First World War it was necessary to pass new laws that would govern in the 2nd Republic of Poland. One of the relatively important issues that needed to be addressed was Polish citizenship. The first part of the paper focuses on the main legal acts that regulated Polish citizenship between 1918 and 1939, with special focus on the Act of 1920 on the Citizenship of the Polish State The outbreak of the Second World War in 1939 changed the geopolitical situation of Poland. However, despite the personal changes in the head state authorities, and the fact that they functioned in very specific conditions, in exile, Polish legislation continued to remain in force. This situation continued throughout the whole period of the Second World War and the Polish authorities in exile regularly referred to the existing regulations, amending them from time to time. One kind of the amended laws were those governing Polish citizenship. The author analyses the circumstances in which the Act on the Revocation of Polish Citizenship of 1938 was repealed by the Polish President in exile in 1941. Further, the main arguments raised in debates on the executive regulation to that Act held by the Second National Council of the Republic of Poland in 1942 and at intra-ministerial sittings in 1944 are presented. The paper also describes the legal position of Poles serving in allied forces, which could in consequence lead to their losing Polish citizenship. Based on the available source material, the methods used by state organs when granting, revoking and restoring Polish citizenship during the Second World War are also analysed.
GRANTING, REVOKING AND RESTORING POLISH CITIZENSHIP
Keywords: Obywatelstwo; Obywatelstwo polskie; II wojna światowa; Nabycie obywatelstwa; Pozbawienie obywatelstwa